NLRP3 Inflammasome Simultaneously Involved in Autophagy and Phagocytosis of THP-1 Cells to Clear Aged Erythrocytes - Qin Li; Fengyong Zhao; Jiamin Zhang; Ying Yang; Zhonghui Guo; Chen Wang; Qixiu Yang; Ying Sun; Ziyan Zhu (Journal of Immunology Research)
Autophagy and phagocytosis are two important processes that capture and digest materials found in cellular interiors and exteriors, respectively. Aged red blood cells (RBCs) are cleared by phagocytes in vivo. We focused on determining whether autophagy occurs after phagocytes swallow sunset erythrocytes, and whether the degree of autophagy is related to scavenging ability of phagocytes to erythrocytes. In addition, the ability of NLR family pyrin domain containing protein 3 (NLRP3) inflammasome to regulate erythrocyte clearance by phagocytes and its association with autophagy-related protein 16-like protein 1 (ATG16L1) are confirmed. We constructed a stable and low-NLRP3 expression THP-1 cell line using CRISPR/Cas9 technology. The analysis of erythrocyte clearance and autophagy of THP-1 cells with low NLRP3 expression showed that autophagy changes together when THP-1 engulfs aged RBCs. The occurrence of autophagy was dominated by microtubule-associated protein 1A/1B-light chain 3- (LC3-) associated phagocytosis accompanied by canonical autophagy. A negative correlation exists between the clearance of RBCs by THP-1 cells and the degree of autophagy. Downregulating the expression of NLRP3 in THP-1 cells can simultaneously inhibit the scavenging ability of THP-1 to erythrocytes and the degree of autophagy. In addition, the autophagy inhibitor bafilomycin A1 (BafA1) can enhance the phagocytosis ability of THP-1 to erythrocytes and promote the NLRP3 activation in THP-1 cells, while the autophagy inducer rapamycin inhibits the phagocytosis ability of THP-1 to RBCs and downregulates the NLRP3 activation. Results showed that autophagy and phagocytosis may be dynamic balance processes that can provide sufficient nutrition and energy to cells. Choosing NLRP3 as a target may regulate the phagocytic ability and the degree of autophagy in the meantime. These findings may be a potential strategy for regulating the clearance rate of phagocytes to aged RBCs and the secretion of proinflammatory cytokines to ensure transfusion safety.